Exhaled aerosols and saliva droplets measured in time and 3D space: Quantification of pathogens flow rate applied to SARS‐CoV‐2 - Adrian Roth; Mehdi Stiti; David Frantz; Andrew Corber; Edouard Berrocal (Natural Sciences, 2023)
Abstract SARS‐CoV‐2 and its ever‐emerging variants are spread from host‐to‐host via expelled respiratory aerosols and saliva droplets. Knowing the number of virions which are exhaled by a person requires precise measurements of the size, count, velocity and trajectory of the virus‐laden particles that are ejected directly from the mouth. These measurements are achieved in 3D, at 15,000 images/s, and are applied when speaking, yelling and coughing. In this study, 33 events have been analysed by post‐processing ∼500,000 images. Using these data, the flow rates of SARS‐CoV‐2 virions have been evaluated. At high concentrations, 107 virions/mL, it is found that 136–231 virions are ejected during a single cough, where the virion flow rate peak is capable of reaching 32 virions within a millisecond. This peak can reach tens of virions/ms when yelling but reduced to only a few virions/ms when speaking. At medium concentrations, ∼105 virions/mL, those results are hundreds of times lower. The total number of virions that are ejected when yelling at 110 dB, instead of speaking at 85 dB, increases by two‐ to threefold. From the measured data analysed in this article, the flow rate of other diseases, such as influenza, tuberculosis or measles, can also be estimated. As these data are openly accessible, they can be used by modellers for the simulation of saliva droplet transport and evaporation, allowing to further advance our understanding of airborne pathogen transmission. Key points Advanced, optimized and combined laser‐based imaging techniques for temporally sizing and tracking respiratory droplets and aerosols. Understanding how pathogens are being ejected from the mouth when speaking, yelling and coughing. Quantifying and analysing the variation of SARS‐CoV‐2 flow rates emission during exhalation.